MAKING THE TEACHING AND LEARNING OF LITERATURE MORE MEANINGFUL - Kurnia Ningsih (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Teaching Literature has good impact to develop students of EFL imagination, culture awareness, even encourage critical thinking. This teaching - learning can construct the students –centered and interactive tenets of Communicative Language teaching ( CLT) . However teachers/lecturers are expected to understand what they are teaching. They are supposed not to focus on teaching – learning method only but also to develop guidance on the analytical methods that are crucial to understand meaning and interprete literary works that lead classroom activities more effective. This paper is going to discuss integrated strategies to improve literary class and make the Teaching- Learning of Literature in Teacher College and University more meaningful.